Peritoneal and plasma D-Lactate concentrations in horses with colic - Yamout, Sawsan Z. (2011)
Objective: To evaluate the association between peritoneal fluid and plasma D-lactate concentration with variables used in the diagnosis and prognosis of horses with colic. Animals: Clinically healthy horses (n=6) and 90 horses with colic. Study Design: Prospective cross-sectional study. Methods: D-lactate concentration was determined in peritoneal fluid and plasma of all horses. Information on other blood and peritoneal fluid variables, signalment, results from the physical examination, outcome, need for surgery, lesion location, and type was retrieved from medical records. Results: Peritoneal D-lactate concentration was strongly correlated with plasma D-lactate concentration (r=0.71; Po.001). Peritoneal and plasma D-lactate concentrations were positively correlated with peritoneal (r=0.8; Po.001) and plasma L-lactate (r=0.33; P=.001) concentrations, respectively. Peritoneal D-lactate concentration was negatively correlated with survival to discharge (U=430.5; Po.001). Median peritoneal D-lactate concentration of horses with septic peritonitis (455.2 mmol/L) and horses with gastrointestinal rupture (599.5 mmol/L) were higher compared with horses with nonstrangulating obstructions (77.7 mmol/L). A cut-off concentration of peritoneal D-lactate of 116.6 mmol/ L had a sensitivity of 0.813 and a specificity of 0.651 to differentiate between nonstrangulating and strangulating obstructions. Conclusions: Peritoneal D-lactate concentration may be more useful for identifying horses with strangulating obstructions (high sensitivity, low probability of a false negative) than to ruling out strangulating obstruction (moderate specificity, high probability of a false positive).